2011
DOI: 10.1089/end.2010.0022
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Renal Descensus for Upper Tract Reconstruction

Abstract: We describe a modern use of laparoscopic renal descensus during the reconstruction of the upper urinary tract. The patient is a 76-year-old mononephric man with recurrent carcinoma in situ in the distal ureter. Using the described technique, we produced an additional 8 to 10 cm of ureteral length and performed a simple ureteroneocystotomy instead of using a traditional psoas hitch and Boari flap creation, bowel interposition, or autotransplantation. Laparoscopic renal descensus is an uncommonly used but simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…For proximal ureteral reconstruction, inferior nephropexy can be used in conjunction with other techniques covering large ureteral defects, up to 12 cm long, reducing the need for bowel interposition. 29,31,45 Although it has been clearly demonstrated that DN is effective and versatile, the adaption of this technique is very limited and review of the current literature reveals a paucity of data regarding urothelial-based reconstructions of the upper and mid-ureter (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For proximal ureteral reconstruction, inferior nephropexy can be used in conjunction with other techniques covering large ureteral defects, up to 12 cm long, reducing the need for bowel interposition. 29,31,45 Although it has been clearly demonstrated that DN is effective and versatile, the adaption of this technique is very limited and review of the current literature reveals a paucity of data regarding urothelial-based reconstructions of the upper and mid-ureter (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…For proximal ureteral reconstruction, inferior nephropexy can be used in conjunction with other techniques covering large ureteral defects, up to 12 cm long, reducing the need for bowel interposition. 29,31,45…”
Section: Discussionmentioning
confidence: 99%
“…It can safely be performed laparoscopically if necessary [33]. The kidney is circumferentially mobilized and pexed to the posterior and lateral body walls as caudal as possible with an absorbable suture.…”
Section: Additional Measuresmentioning
confidence: 99%